Burden of arrhythmia in recreational marijuana users. (1st August 2018) - Desai, Rupak; Patel, Upenkumar; Deshmukh, Abhishek; Sachdeva, Rajesh; Kumar, Gautam
Abstract: Marijuana or Cannabis is extensively used as a recreational substance globally. Case reports have reported cardiac arrhythmias immediately following recreational marijuana use. However, the burden of arrhythmias in hospitalized marijuana users have not been evaluated through prospective or cross-sectional studies. Therefore, we planned to measure temporal trends of the frequency of arrhythmias in hospitalized marijuana users using National Inpatient Sample (NIS) database in the United States. Highlights: Total of 2.7% of recreational marijuana users developed arrhythmia with a steadily increasing trend from 2010 through 2014. Atrial fibrillation was the most common subtype arrhythmia among hospitalized marijuana users. The incidence of arrhythmia in male and female marijuana users nearly increased two-fold between 2010 and 2014. The all-cause in-hospital mortality in marijuana users with arrhythmias increased from 3.7% in 2010 to 4.4% in 2014.